Investigation of coaching experience periods of UEFA european football champion national team head coaches - YORULMAZLAR, MEHMET MUSTAFA (My University, 2022)
The purpose of this research is to investigate how long it takes for the national team head coaches to win the UEFA European Football Championship between 1960-2021 to turn into competence and ultimately superior success. The model of the research was determined as "Basic Qualitative Research". The data collection technique was determined as "Document Analysis". The universe of the research consists of the national teams that won the UEFA European Football Championship finals between 1960-2021. The sample of the research consisted of the coaches of the national teams that showed the success of reaching the summit in the UEFA European Football Championship finals. Written documents related to the UEFA European Football Championship finals were used in the data analysis of the research. The general experience periods of the national team coaches who were successful in the UEFA European Football Championship finals were determined on the basis of the date they started their coaching profession, and it was determined that they were active within the general working period. Coaching times were calculated and compared and analyzed. With this study, it was examined what kind of experience the elite national team coaches had before they reached their career peak. After an average experience period, it was seen that the general coaching experience and active working time of the coaches who started to work in the national teams were high

Bu araştırmanın amacı, 1960-2021 yılları arasında UEFA Avrupa Futbol Şampiyonası’nı kazanan milli takım baş antrenör deneyimlerinin, yetkinliğe ve nihayetinde üstün başarıya ne kadar sürede dönüştüğünün araştırılmasıdır. Araştırmanın modeli “Temel Nitel Araştırma” olarak belirlenmiştir. Veri toplama tekniği "Doküman Analizi" olarak belirlenmiştir. Araştırmanın evrenini 1960-2021 yılları arasında UEFA Avrupa Futbol Şampiyonası finallerinde şampiyon olan milli takımlar oluşturmaktadır. Araştırmanın örneklemini ise UEFA Avrupa Futbol Şampiyonası finallerinde zirveye ulaşma başarısını gösteren milli takımların teknik direktörleri oluşturmuştur. Araştırmanın veri analizinde UEFA Avrupa Futbol Şampiyonası finallerine ilişkin yazılı belgeler kullanılmıştır. UEFA Avrupa Futbol Şampiyonası finallerinde başarılı olan milli takım antrenörlerinin, antrenörlük mesleğine başladıkları tarih esas alınarak genel deneyim süreleri belirlenerek, genel çalışma süresinin içerisinden aktif olarak antrenörlük süreleri hesaplanarak karşılaştırma yapılıp analiz edildi. Bu çalışma ile, elit milli takım teknik direktörlerinin kariyer zirvesine ulaştıkları bir kupa öncesi nasıl bir deneyim süresi geçirdikleri incelendi. Ortalama bir deneyim sürecinin ardından milli takımlarda göreve başlayan koçların, genel deneyimlerinin ve aktif çalışma sürelerinin yüksek olduğu görüldü.
UEFA Avrupa futbol şampiyonu milli takım teknik direktörlerinin antrenör deneyim sürelerinin incelenmesi
Keywords: National Team; Football; Coaching; Experience; Milli Takım; Futbol; Koçluk; Deneyim